Internalizing Multicultural and Intercultural Values of Religious Moderation through Islamic Education to Strengthen National Character - Ani Rindiani; Sahudi Sahudi; Yayat Hidayatulloh; Mukhsin Mukhsin (Dinamika Ilmu, 2026)
This study analyzes the process of Islamic religious education learning in internalizing religious moderation values at SMK Al-Falah Nagreg, Bandung Regency. The research employs a qualitative approach with a descriptive case study design. Data were collected through participatory observation, in-depth interviews with five Islamic religious education teachers and fifteen students, and curriculum document analysis. The findings suggest that value internalization was facilitated through an inclusive curriculum approach, interactive experiential learning methods, and an authentic evaluation system focused on attitudes. A key finding reveals that the school environment, integrated with a pesantren (Islamic boarding school), creates a unique ecosystem where moderation values are not only taught but also lived in daily interactions. The study concludes that holistic, contextual learning in Islamic religious education can serve as an effective model for shaping a tolerant and inclusive national character. Research implications include recommendations for developing teacher-training modules based on interfaith dialogue and for more systematically integrating moderation values into the Merdeka Curriculum.